Bibliometric Analysis of the Literature on Carbon Ion Therapy Using VOSviewer Software and Dimensions Database - El Bekkouri, H.; Al Ibrahmi, E.; El-Asery, M.; Bardane, A.; Didi, A.; El Mahjoub, C.; Sadoune, Z. (Atom Indonesia, 2024)
This study aims to carry out a bibliometric assessment of the worldwide research literature and historical research results on carbon ion therapy for cancer treatment. To carry out this work, we used the VOSviewer software and the Dimensions database. The VOSviewer software tool examined 2,500 publications exported from the Dimensions database. The results show a notable upward trajectory in academic research on carbon ion therapy since 1994, with 2020 showing the highest volume of publications. “Biomedical and Clinical Sciences”, “Physical Sciences”, “Oncology and Carcinogenesis”, and “Medical and Biological Physics” are the most important research categories. “Physics in Medicine and Biology” and “Medical Physics” are the leading journals for research publications on carbon ion therapy. Scrutiny based on term occurrences demonstrates the shift in research interest towards carbon ion radiation therapy. The analysis of bibliographic couplings concerning different countries revealed that Japan is the most dynamic and prolific country based on the number of publications (659) and citations (13734), followed by Germany with 590 publications and 19679 citations. These analytical studies provide a thorough overview of academic publications dedicated to using carbon ions for tumor treatment. This data is anticipated to be highly valuable for researchers seeking to pinpoint the most recent developments and emerging trends in this field of research.